Differential effects of saturated and unsaturated fatty acids on autophagy in pancreatic β-cells. (November 2019) - Dhayal, Shalinee; Zummo, Francesco P; Anderson, Matthew W; Thomas, Patricia; Welters, Hannah J; Arden, Catherine; Morgan, Noel G
Abstract : Long-chain saturated fatty acids are lipotoxic to pancreatic β-cells, whereas most unsaturates are better tolerated and some may even be cytoprotective. Fatty acids alter autophagy in β-cells and there is increasing evidence that such alterations can impact directly on the regulation of viability. Accordingly, we have compared the effects of palmitate (C16:0) and palmitoleate (C16:1) on autophagy in cultured β-cells and human islets. Treatment of BRIN-BD11 β-cells with palmitate led to enhanced autophagic activity, as judged by cleavage of microtubule-associated protein 1 light chain 3-I (LC3-I) and this correlated with a marked loss of cell viability in the cells. In addition, transfection of these cells with an mCherry-YFP-LC3 reporter construct revealed the accumulation of autophagosomes in palmitate-treated cells, indicating an impairment of autophagosome-lysosome fusion. This was also seen upon addition of the vacuolar ATPase inhibitor, bafilomycin A1. Exposure of BRIN-BD11 cells to palmitoleate (C16:1) did not lead directly to changes in autophagic activity or flux, but it antagonised the actions of palmitate. In parallel, palmitoleate also improved the viability of palmitate-treated BRIN-BD11 cells. Equivalent responses were observed in INS-1E cells and in isolated human islets. Taken together, these data suggest that palmitate may cause an impairment of autophagosome-lysosome fusion. These effects were not reproduced by palmitoleate which, instead, antagonised the responses mediated by palmitate suggesting that attenuation of β-cell stress may contribute to the improvement in cell viability caused by the mono-unsaturated fatty acid.